2000
DOI: 10.1074/jbc.m004897200
|View full text |Cite
|
Sign up to set email alerts
|

The BNIP-2 and Cdc42GAP Homology Domain of BNIP-2 Mediates Its Homophilic Association and Heterophilic Interaction with Cdc42GAP

Abstract: We recently showed that BNIP-2 is a putative substrate of the fibroblast growth factor receptor tyrosine kinase and it possesses GTPase-activating activity toward the small GTPase, Cdc42. The carboxyl terminus of BNIP-2 shares high homology to the non-catalytic domain of Cdc42GAP, termed BCH (for BNIP-2 and Cdc42GAP homology) domain. Despite the lack of obvious homology to any known catalytic domains of GTPase-activating proteins (GAPs), the BCH domain of BNIP-2 bound Cdc42 and stimulated the GTPase activity v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 44 publications
(65 reference statements)
0
75
0
Order By: Relevance
“…† Survival rate at weaning. RhoGAP domain that was shown to be catalytically specific toward Cdc42 over other Rho GTPases (16,17) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…† Survival rate at weaning. RhoGAP domain that was shown to be catalytically specific toward Cdc42 over other Rho GTPases (16,17) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Among the large number of RhoGAP family members, Cdc42GAP appears to favor Cdc42 as a substrate over other Rho GTPases in vitro (16,17), but its physiologic role has yet to be verified in vivo. We found that Cdc42GAP Ϫ/Ϫ mice have significantly reduced body and organ sizes, similar to that of the p190-B RhoGAP knockouts (18).…”
mentioning
confidence: 99%
“…For example, an arginine-finger patch in BNIP-2 is necessary for its GAP-like activity or the other distinct region for its homophilic/heterophilic interactions (Low et al, 2000a). Likewise, a distinct region in BNIP-Sa BCH domain is also involved in conferring homophilic binding and this sequence is also required for its cell rounding and apoptotic effects (Zhou et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent to our previous report, the DB mutant without the homophilic-interacting motif could not be precipitated by GST-BNIP-Sa whereas the DA/ext-RBD mutant still retained its ability to interact with the wildtype BNIP-Sa. To further confirm their interaction in vivo, 293T cells were co-transfected with an HA-RhoA expression plasmid together with either the FLAGtagged full-length, DA/ext-RBD mutant or the DB mutant and subjected to co-immunoprecipitation assays (Figure 4f Presence of a cryptic GAP-binding motif that overlaps with minimal Rho-binding region in the BCH domain of BNIP-Sa Our previous reports had shown that both BNIP-2 and BNIP-Sa could bind p50RhoGAP via their respective BCH domains (Low et al, 2000a;Zhou et al, 2002). In this regard, we proceeded to identify the binding motif for p50RhoGAP within the BNIP-Sa BCH domain by first subjecting the above two mutants (DA/ext-RBD and DB) and the wild-type BNIP-Sa to co-immunoprecipitation studies in vivo.…”
Section: Bnip-sa Specifically Interacts With Rhoamentioning
confidence: 99%
“…Transfected 293T cells were lysed with RIPA buffer [150 mM NaCl, 50 mM TrisHCl pH 7.3, 0.25 mM EDTA, 1% (w/v) sodium deoxycholate, 1% (v/v) Triton X-100, 50 mM NaF, 5 mM sodium orthovanadate, protease inhibitors (Roche Applied Science)] and directly analyzed as whole-cell lysates or aliquots used for pull-down with various GST fusion proteins (20 mg) or anti-Flag M2 affinity gel (Sigma), as previously described (Low et al, 2000). Samples were run in SDS-PAGE gels followed by western blot analyses using the Pierce Pico ECL (Thermo Scientific).…”
Section: Co-immunoprecipitation Pull-down and Western Blot Analysesmentioning
confidence: 99%